A CMIP6 assessment of the potential climate change impacts on solar photovoltaic energy and its atmospheric drivers in West Africa. (1st April 2022) - Danso, Derrick Kwadwo; Anquetin, Sandrine; Diedhiou, Arona; Lavaysse, Christophe; Hingray, Benoit; Raynaud, Damien; Kobea, Arsène Toka
Abstract: Many solar photovoltaic (PV) energy projects are currently being planned and/or developed in West Africa to sustainably bridge the increasing gap between electricity demand and supply. However, climate change will likely affect solar power generation and the atmospheric factors that control it. For the first time, the state-of-the-art CMIP climate models (CMIP6) are used to investigate the potential future evolution of solar power generation and its main atmospheric drivers in West Africa. A multi-model analyses carried out revealed a decrease of solar PV potential throughout West Africa in the 21st century, with an ensemble mean reduction reaching about 12% in southern parts of the region. In addition, the variability of future solar PV production is expected to increase with a higher frequency of lower production periods. The projected changes in the solar PV production and its variability are expected to be predominant in the June to August season. We found the decrease in the solar PV potential to be driven by a decrease of surface irradiance and an increase of near-surface air temperature. However, the decrease of the surface irradiance accounted for a substantially larger percentage of the projected solar PV potential. The decrease in surface irradiance was further linked to changes in both cloud cover and aerosol presence, although generally much more strongly for the former.